Neuropsychiatry of Parkinson's disease Neuropsiquiatria da doença de Parkinson - Arthur Kummer; Antonio Lucio Teixeira (Arquivos de Neuro-Psiquiatria)
Parkinson's disease (PD) is traditionally regarded as a movement disorder. In recent years, however, non-motor symptoms have been considered significant factors of disability at all stages of the illness. Behavioral and psychological symptoms or neuropsychiatric syndromes associated with PD are frequent and may represent a challenge in the management of these patients. They include anxiety, depression, psychosis, sleep, sexual and impulse control disorders, apathy and cognitive dysfunction. Their pathogenesis in PD is complex, involving neurodegenerative, drug-related and psychological mechanisms. We will review the current knowledge of this growing field, also focusing on the management of theses syndromes. A doença de Parkinson (DP) é tradicionalmente conhecida como um distúrbio do movimento. Entretanto, os sintomas não-motores têm sido considerados recentemente como fatores relevantes de incapacidade em todos os estágios da doença. Sintomas motores e comportamentais ou síndromes neuropsiquiátricas associadas à DP são frequentes e seu manejo pode se tornar um verdadeiro desafio. São comuns quadros de ansiedade, depressão, psicose, distúrbios do sono, transtornos do controle do impulso, apatia e disfunções cognitivas. A patogênese desses transtornos na DP é complexa, envolvendo mecanismos degenerativos, psicológicos e relacionados ao tratamento. Neste artigo, revisamos o estado do conhecimento desse campo de interesse crescente, também enfocando o manejo dessas síndromes.